Cross-protection of commercial vaccines against Chilean swine influenza A virus using the guinea pig model as a surrogate - Tapia, Rodrigo; Mena, Juan; García, Victoria; Culhane, Marie; Medina, Rafael A.; Neira, Victor (Frontiers in Veterinary Science, 2023)
Influenza A virus poses a significant threat to public health and the swine industry. Vaccination is the primary measure for controlling the disease, but the effectiveness of vaccines can vary depending on the antigenic match between vaccine strains and circulating strains. In Chile, H1N1pdm09 and other lineages H1N2 and H3N2 have been detected in pigs, which are genetically distinct from the strains included in commercial vaccines. This study aimed to evaluate the cross-protection by commercial vaccines against strains circulating in Chile using the guinea pig model. For this study, four circulating strains (A/swine/Chile/H1A-7/2014(H1N2), A/swine/Chile/H1B-2/2014(H1N2), A/swine/Chile/H1P-12/2015(H1N1), and A/swine/Chile/H3-2/2015(H3N2)) were selected. Guinea pigs were divided into vaccinated and control groups. The vaccinated animals received either a multivalent antigenically heterologous or monovalent homologous vaccine, while the control animals remained unvaccinated. Following vaccination, all animals were intranasally challenged, and nasal wash samples were collected at different time points post-infection. The results showed that the homologous monovalent vaccine-induced hemagglutinin-specific antibodies against the Chilean pandemic H1N1pdm09 strain. However, the commercial heterologous multivalent vaccine failed to induce hemagglutinin-specific antibody titers against the H1N2 and H3N2 challenge strains. Furthermore, the homologous monovalent vaccine significantly reduced the duration of viral shedding and viral titers specifically against the Chilean pandemic H1N1pdm09 strain and heterologous multivalent vaccine only partial. These findings highlight the importance of regularly updating vaccine strains to match the circulating field strains for effective control of swine influenza. Further research is needed to develop vaccines that confer broader protection against diverse strains of swine influenza A virus.